Developing knowledge communities through partnerships for literacy - Auzenne-Curl, Chestin; Craig, Cheryl J. (Advances in research on teaching ;, 2021)
Developing Knowledge Communities through Partnerships for Literacy explores the development of knowledge communities - safe spaces on the educational landscape - where research and professional development with literacy teachers and writers can unfurl. This volume, inspired by an evaluation research partnership involving professional development for writing instructors, coheres around Dewey's three-dimensional threads of experience. Contributing authors give attention to the temporal, situational, and social implications of teachers' organically formed knowledge communities. This book is essential reading for researchers of education, knowledge communities and cross-institutional research partnerships as it: inquires into the historical roots of research partnerships offers unique perspectives on literacy coaching and professional development in public education, and includes uniquely divergent threads from researchers in the field. Each -- Chapter calls readers to reflect on the influence of community, identity and change on reform efforts in education.